2021
DOI: 10.3389/fmicb.2021.747019
|View full text |Cite
|
Sign up to set email alerts
|

Combating Drug-Resistant Bacteria Using Photothermally Active Nanomaterials: A Perspective Review

Abstract: Injudicious use of antibiotics has been the main driver of severe bacterial non-susceptibility to commonly available antibiotics (known as drug resistance or antimicrobial resistance), a global threat to human health and healthcare. There is an increase in the incidence and levels of resistance to antibacterial drugs not only in nosocomial settings but also in community ones. The drying pipeline of new and effective antibiotics has further worsened the situation and is leading to a potentially “post-antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 156 publications
(183 reference statements)
0
31
0
Order By: Relevance
“…Several studies showed that antibacterial agents tend to act more strongly on Gram-positive than on Gram-negative bacteria. It is probably due to the differences in cell wall composition and structure since Gram-negative bacteria possess an outer membrane [41].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that antibacterial agents tend to act more strongly on Gram-positive than on Gram-negative bacteria. It is probably due to the differences in cell wall composition and structure since Gram-negative bacteria possess an outer membrane [41].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the advantages of this approach include the requirement of a low amount of AMP-NPs to kill bacteria, the inability of the bacteria to develop antimicrobial resistance and a wide range of antimicrobial activity against nosocomial and MDR bacteria. 87 Considering the advantage of the photothermal therapy (PTT) approach, Chen's group prepared Van conjugated Au nanotriangles (Van@Au NTs), which had potent antimicrobial activity against several strains of bacteria and Van-resistant bacteria upon exposure to a 808 nm near infrared (NIR) light compared to Van@Au NTs without NIR light exposure. 88,89 Au NTs increase the temperature of the reaction solution to 50 1C after 5 min of NIR light exposure; however, the local temperature near the bacterial cell wall could be higher than 50 1C due to the stronger binding of Au NTs with the bacterial membrane.…”
Section: Amp-based Metallic and Inorganic Npsmentioning
confidence: 99%
“…However, the photothermal killing approach does not have superior antimicrobial efficiency compared to antimicrobial agents. 87 The antimicrobial efficacy could be enhanced by the addition of antimicrobial agents such as AMPs. It may be possible that photothermal energy compromises the integrity of the bacterial membrane and facilitates AMPs to form pore-like structures rapidly, leading to the leakage of cellular content and bacterial death.…”
Section: Amp-based Nanoformulations and Their Antimicrobial Propertiesmentioning
confidence: 99%
“…Bioremediation, biomaterials and biomolecules During the past 50 years, microbiology has played a vital role in solving human grand challenges in fields such as health, agriculture, food security, waste management, among others (Thallinger et al, 2013, Singh et al, 2016, De Giani et al, 2021, Fu et al, 2021, Gilmour et al, 2021, Iyer et al, 2021, Kaur et al, 2021, Soh et al, 2021, Montano Lopez et al, 2022. The economic benefit of inhabiting a microbial world is manyfold and accounts for billions of euros annually (Anand et al, 2021).…”
Section: Solution Through Microbiologymentioning
confidence: 99%